CLINICAL PROFILE OF MOTHER WITH HUMAN IMMUNODEFICIENCY VIRUS AND ITS FETOMATERNAL OUTCOME - HETAXI A CHHETA; HARSHDEEP K JADEJA; BHAVESH B AIRAO (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: Human immunodeficiency virus (HIV) infection carries many high-risk conditions in pregnancy. Our study aims to analyze the clinical profile of HIV-pregnant women and to determine the fetomaternal outcomes among HIV-positive pregnancies. Methods: This study is a retrospective observational study carried out at C U Shah Medical College and Hospital, Surendranagar, Gujarat, covering data of all pregnant women with HIV who delivered between January 2018 and December 2022. Results: Among a total of 8881 patients delivered from January 2018 to December 2022, 56 mothers with HIV positivity gave birth. 80% of HIV-positive mothers are between 21 and 30 years of age group. Among all HIV-positive pregnant patients, 30% were diagnosed during pregnancy, and 75% were taking regular antenatal care (ANC) visits. A total of 60% of HIV-positive patients were undergone vaginal delivery, and 40% underwent lower segment cesarean section. Among all HIV-positive pregnant patients, different maternal complications were found in 65% of the population. A total of 1.8% of babies are positive with HIV at 6-week postpartum intervals through mother-to-child transmission (MTCT). Discussion: The study analyzed the 5-year clinical profile of HIV-positive mothers and their fetomaternal outcomes. The findings from the study reveal important facets related to maternal health and neonatal outcomes, the impact of antiretroviral therapy (ART), and the prevention of MTCT of HIV. Conclusion: This study brings out the clinical profile and fetomaternal outcomes of HIV-positive mothers over 5 years, with a special emphasis on the role of ANC and ART in improving outcomes. Early diagnosis of HIV infection, regular ANC, and strict adherence to ART reduce complications and improve outcomes.